2019
DOI: 10.18203/2320-1770.ijrcog20190273
|View full text |Cite
|
Sign up to set email alerts
|

Kidney length, a visceral parameter predicts foetal age between 24 to 40 weeks of gestation

Abstract: Background: Accurate estimation of gestational age is important in providing appropriate antenatal care. Recent evidence suggests that weightage should also be given to kidney length in addition to standard biometric parameters in determining the duration of pregnancy by ultrasound.Methods: In a single centre, prospective cross-sectional study was done in 120 pregnant women. In addition to standard biometric parameters, kidney length was also measured between 24 to 40 weeks at two-week intervals. A total of 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, none has been reported to be the most accurate or reliable for estimating GA. In fact, Benson and Doubilet reported that the accuracy of ultrasound foetal biometric measurements decreases as pregnancy advances ( 6 ) Other authors ( 7 , 8 ) have suggested that using a combination of these surrogate foetal measurements is more accurate than using each in isolation, and yet, others ( 5 , 9 ) have opined that FKL appears to be a better measure for GA. So, even if it is clear that sonography of foetal kidney size is of benefit for detecting foetal kidney abnormalities, its use as a potential ‘stand-alone’ measure to estimate GA of pregnancy, especially when dates are unsure, needs further evaluation ( 5 , 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, none has been reported to be the most accurate or reliable for estimating GA. In fact, Benson and Doubilet reported that the accuracy of ultrasound foetal biometric measurements decreases as pregnancy advances ( 6 ) Other authors ( 7 , 8 ) have suggested that using a combination of these surrogate foetal measurements is more accurate than using each in isolation, and yet, others ( 5 , 9 ) have opined that FKL appears to be a better measure for GA. So, even if it is clear that sonography of foetal kidney size is of benefit for detecting foetal kidney abnormalities, its use as a potential ‘stand-alone’ measure to estimate GA of pregnancy, especially when dates are unsure, needs further evaluation ( 5 , 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%